Effect of hardening holding time and tempering duration on the microstructure and hardness of CHQ 10B21 wire - Melya D. Sebayang; Kimar Turnip (Politeknik Negeri Lhokseumawe, 2026)
Heat treatment parameters play an important role in controlling the mechanical properties and microstructure of bolt materials. The research was conducted on the production of bolts produced from raw material wire CHQ 10B21. This study aims to evaluate the effect of hardening holding time and tempering duration on the hardness, tensile strength, and microstructure of CHQ 10B21 wire used for bolt production. The material was heated at 870°C with varying holding times, followed by oil quenching and tempering at 480°C with different tempering durations. Hardness testing was evaluated based on the HES D3211-99A standard with a target range of 22–32 HRC, while metallographic observations were conducted using sequential grinding and polishing. The results showed a direct relationship between holding time, tempering duration, and material properties. Longer hardening holding time increased hardness, with the highest value of 29 HRC obtained at 60 minutes, compared with 14 HRC in the raw material. Increasing tempering time improved tensile strength, reaching 891.91 N/mm² at 75 minutes after 60 minutes of hardening. Microstructural analysis showed the formation of tempered martensite and tempered bainite, with more homogeneous phase distribution at longer heat-treatment durations. These findings indicate that the optimal heat treatment condition for CHQ 10B21 bolt production is 60 minutes hardening followed by 75 minutes tempering.